de o resultado de cada multiplicação com o cálculo,
(-9)•(+12)•(-2)
(-7)•(-10)•(-5)
(-7)•(-7)•(-1)•(-5)
(-20)•(-2)•(+6)•(+4)•(-1)
Soluções para a tarefa
Respondido por
2
Oiii, segue resolução !!!
Anexos:
![](https://pt-static.z-dn.net/files/d47/8b448392ad56c729978da672954b0ef5.png)
Respondido por
0
Resposta:
(-9)*(+12)*(-2)
=-108*(-2)
=216
(-7)*(-10)*(-5)
=70*(-5)
=-350
(-7)*(-7)*(-1)*(-5)
=49*(-1)*(-5)
=49*5
=245
(-20)*(-2)*(+6)*(+4)*(-1)
=40*24*(-1)
-960
Espero ter ajudado!!!
Perguntas interessantes
Inglês,
9 meses atrás
Português,
9 meses atrás
Ed. Física,
9 meses atrás
Sociologia,
11 meses atrás
História,
11 meses atrás
Geografia,
1 ano atrás
ENEM,
1 ano atrás
Lógica,
1 ano atrás